REVISITING THE IMPACT OF INFOTAINMENT AND IRRITATION ON MOBILE TEXT ADVERTISEMENT PURCHASE INTENTION - Saleh, Muhammad; Junejo, Ikramuddin (The journal of contemporary issues in business and government, 2021)
The purpose for this study is to analyze reinvesting the impact of infotainment and irritation on mobile text purchase intention the impact of mobile text (SMS) advertisement purchase intention in Hyderabad, Pakistan. They were considered to generate variables which had impact on for purchase intention through mobile text (SMS) advertisement including Infotainment and Irritation. This study surveyed 200major cities of Sindh, Hyderabad and Karachi. Data was collected through convenience sampling; structured questionnaire survey was use as a tool to collect the data from respondents and five point likert scale used as measurement scale. Reliability test and Multivariable linear regression was used for the calculation of the data and the following outcomes were formed. The result of this study shows that Infotainment has positive and significant impact on mobile text (SMS) advertisement purchase intention. However, Irritation has negative and significant impact on mobile text (SMS) advertisement purchase intention. Based on these findings it is highly suggested that marketers should avoid the repetitive SMS via mobile because customer get irritation and avoid buying goods and services for related brand.